2016
DOI: 10.1007/s40069-016-0133-z
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of RC Beam Strengthened by Partially De-bonded Near Surface-Mounted FRP Strip

Abstract: This paper presents an experimental work to study the flexural strength of reinforced concrete (RC) beams strengthened by partially de-bonded near surface-mounted (NSM) fiber reinforced polymer (FRP) strip with various de-bonded length. Especially, considering high anchorage capacity at end of a FRP strip, the effect of de-bonded region at a central part was investigated. In order to check the improvement of strength or deformation capacity when the bonded surface area only increased without changing the FRP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…According to the aforementioned analysis procedures, calculations were performed with specimens of Seo et al [24], and the adequacy of the analysis method was compared. The details of the specimens are shown in Fig.9 and Table 1.…”
Section: Analysis Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the aforementioned analysis procedures, calculations were performed with specimens of Seo et al [24], and the adequacy of the analysis method was compared. The details of the specimens are shown in Fig.9 and Table 1.…”
Section: Analysis Results and Discussionmentioning
confidence: 99%
“…Fig. 1 is a picture showing the results of an experiment conducted by Seo et al [24], and as shown in the figure, the failure is concentrated in the central part of the beam in the case of the full bonding, whereas cracks are distributed at appropriate intervals in the case of the de-bonding at the central part. It means that a slightly ductile behavior can be induced with an increase in the uniform deformation of FRP.…”
mentioning
confidence: 98%
“…Besides FRP laminate, to avoid the exposure of repair materials, there has been growing interest in the application of near-surface mounted (NSM) FRP bars or strips to repair and retrofit concrete bridge girders. Studies have shown that the behavior of concrete beams strengthened by NSM FRP strips/bars was significantly improved (Andrawes et al, 2018; Barros and Dias, 2006; Bilotta et al, 2015; El-Hacha and Rizkalla, 2004; Jalali et al, 2012; Nanni et al, 2004; Nordin and Täljsten, 2006; Rahal and Rumaih, 2011; Seo et al, 2016). In addition to non-prestressing repair methods, researchers have also studied using prestressing techniques to repair and strengthen the flexural behavior of concrete bridge girders using either FRP tendons or prestressing strands (Harries et al, 2009; Kim et al, 2008; Wu et al, 2014, among many others).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of investigations relating to partially bonded systems have focused on the analysis of short-term performance and ductility [10,21,22,23]. Chahrour and Soudki [21] reported that partially bonded CFRP reinforcements performed better than a fully bonded system of CFRP reinforcements, in terms of the load carrying capacity and ductility, which revealed that end-anchored, partially bonded CFRP reinforcements significantly enhanced the ultimate capacity, compared to that of a fully bonded system.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that ductility increased together with unbonded length, since the internal slip of the FRP bar and gradual concrete failure occurred near the ultimate stage, which led to the nonlinear behavior of the beams. Information on the short-term behavior of RC beams, prestressed with FRP reinforcement, is relatively abundant [6,10,21,23,24,25,26]. However, there is a lack of research investigating fatigue performance of concrete beam prestressed with partially bonded FRP tendons.…”
Section: Introductionmentioning
confidence: 99%